Pengetahuan Dalam Penggunaan Sunscreen Pada Mahasiswa Fakultas Pariwisata Dan Perhotelan - Susiladani Susiladani; Dian Ramadani; Hilmi Habibah; Siska Miga Dewi (Tamasya : Jurnal Pariwisata Indonesia, 2024)
Indonesia, as a tropical country, faces a high risk from ultraviolet (UV) radiation that can damage skin and health. This study aims to evaluate the knowledge and behavior regarding sunscreen use among students of the Faculty of Tourism and Hospitality. The method used is a survey with questionnaires distributed to respondents. Results indicate that although students are aware of the importance of using sunscreen, the usage rate remains low, and many do not choose safe products. These findings highlight the need for increased knowledge about proper sunscreen selection and the dangers of UV exposure. The implications of this research emphasize the importance of further education on correct sunscreen use, as well as the necessity for outreach activities to raise awareness about skin protection from sun exposure. Thus, it is hoped that adolescents can better maintain their skin health and reduce the risk of diseases caused by excessive UV exposure.